UPAYA PENCEGAHAN STUNTING DENGAN OPTIMALISASI PERAN POSYANDU - Ana Faizah; Ratna Dewi Silalahi; Nurhafizah Nasution; Herliana Bakri (LPPM STIKes MERCUBAKTIJAYA Padang, 2022)
Background : Indonesia is faced with a double burden, apart from facing malnutrition, stunting and anemia, at the same time it also faces the problem of obesity. The prevalence of stunting in Indonesia was 30%-39%. As Nawacita the President of the Republic of Indonesia, stunting is contained in the 2020-2024 RPJMN with a target of reducing prevalence to 14%. The number of stunting cases in the Batam Kepulauan Riau Province in 2020 was 7.2%. Based on a preliminary study, it was noted that 7 toddlers were stunted. Method: Stunting prevention efforts through a partnership program in the form of counseling and training on the cultivation of ikan tamban menari as processed food ingredients for fish crackers and nuggets, then empowerment as an effort to increase public awareness, and good parenting in fulfilling nutrition, growth and development of toddlers. Activities carried out during December 2021 have had positive impacts and results in the form of providing complementary feeding, increasing public awareness, and implementing parenting patterns. Result: Optimizing the role of posyandu through this partnership program can be well received by the community, cadres and posyandu partners as targets. This program is expected to run well and sustainably